2015
DOI: 10.1088/1742-5468/2015/06/p06025
|View full text |Cite
|
Sign up to set email alerts
|

Non-affine fluctuations and the statistics of defect precursors in the planar honeycomb lattice

Abstract: Certain localised displacement fluctuations in the planar honeycomb lattice may be identified as precursors to topological defects. We show that these fluctuations are among the most pronounced non-affine distortions of an elemental coarse graining volume of the honeycomb structure at non zero temperatures. We obtain the statistics of these precursor modes in the canonical ensemble, evaluating exactly their single point and two-point spatio-temporal distributions, for a lattice with harmonic nearest neighbour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…In earlier work, it was demonstrated that local displacements of particles in a crystal away from their ideal positions may be decomposed into affine and non-affine components [10][11][12]. External stress couples to the affine part of the displacements.…”
Section: Introductionmentioning
confidence: 99%
“…In earlier work, it was demonstrated that local displacements of particles in a crystal away from their ideal positions may be decomposed into affine and non-affine components [10][11][12]. External stress couples to the affine part of the displacements.…”
Section: Introductionmentioning
confidence: 99%
“…An advantage of studying the properties of a solid using a harmonic approximation is the possibility of obtaining exact results even in the presence of the non-affine field h X . Indeed, the complete statistical mechanics of this system can be obtained analytically (apart from numerical integrals and Fourier transforms) [18][19][20] as long as the periodic crystalline phase is stable. In order to understand how crystal properties are affected by the non-affine field, h X , we calculate the Hessian D(R, R ) = ∂ 2 H/∂u(R)∂u(R ).…”
Section: Resultsmentioning
confidence: 99%
“…While [18] gave the general theory and specific examples of the one dimensional chain and the two dimensional triangular lattice, [20] extended this formalism to the two dimensional honey-comb structure. Below, we give a brief summary of this procedure for completeness.…”
Section: Non-affine Fluctuationsmentioning
confidence: 99%
See 2 more Smart Citations